2022
DOI: 10.1021/acsami.1c22730
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and Failure Mechanisms of Thermoelectric Type-I Clathrate Ba8Au6Ge40

Abstract: Type-I clathrate Ba 8 Au 6 Ge 40 , possessing an interesting structure stacked by polyhedrons, is a potential "phonon-glass, electron-crystal" thermoelectric material. However, the mechanical properties of Ba 8 Au 6 Ge 40 vital for industrial applications have not been clarified. Here, we report the first density functional theory calculations of the intrinsic mechanical properties of thermoelectric clathrate Ba 8 Au 6 Ge 40 . Among the different loading directions, the {110}/⟨001⟩ shearing and ⟨110⟩ tension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 54 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…By comparing the failure mechanism of Ba 8 Au 6 Si 40 and Ba 8 Au 6 Ge 40 , it is found that the Ge pentagonal ring in Ba 8 Au 6 Ge 40 is a relatively flexible structure, with the Ge–Ge bond elongating and softening during the shear deformation. Moreover, the brittle failure of CoSb 3 is mainly attributed to the deconstruction of the Sb-ring and the collapse of the Co–Sb frameworks .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By comparing the failure mechanism of Ba 8 Au 6 Si 40 and Ba 8 Au 6 Ge 40 , it is found that the Ge pentagonal ring in Ba 8 Au 6 Ge 40 is a relatively flexible structure, with the Ge–Ge bond elongating and softening during the shear deformation. Moreover, the brittle failure of CoSb 3 is mainly attributed to the deconstruction of the Sb-ring and the collapse of the Co–Sb frameworks .…”
Section: Resultsmentioning
confidence: 99%
“…Here, we compare the intrinsic mechanical properties of type-I and type-VIII clathrates with those of other important TE materials, as shown in Figure . The red column represents the ideal shear strength of the TE clathrates, which shows the disperse distribution of clathrate ideal strength among all important TE materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported the intrinsic mechanical properties of typical TE materials including type-I clathrate Ba 8 Au 6 Ge 40 in previous work. 21 Compared with the type-I clathrates with complete cage frameworks, tI-Na 2 ZnSn 5 has an incomplete open cage framework. Pores and tunnels may result in the change of intrinsic mechanical properties, such as degradation of ideal strength and mechanical anisotropy.…”
Section: Introductionmentioning
confidence: 99%